2017
DOI: 10.1021/acs.nanolett.7b02600
|View full text |Cite
|
Sign up to set email alerts
|

Inversion Domain Boundary Induced Stacking and Bandstructure Diversity in Bilayer MoSe2

Abstract: Interlayer rotation and stacking were recently demonstrated as effective strategies for tuning physical properties of various two-dimensional materials. The latter strategy was mostly realized in heterostructures with continuously varied stacking orders, which obscure the revelation of the intrinsic role of a certain stacking order in its physical properties. Here, we introduce inversion-domain-boundaries into molecular-beam-epitaxy grown MoSe2 homobilayers, which induce uncommon fractional lattice translation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 51 publications
8
51
1
Order By: Relevance
“…The rst grain boundaries (denoted as yellow lines) are composed of the chains of 4-fold rings (4|4) with point-sharing at a common Se site. This type of phase boundary has been previously observed in grain boundary of CVD-grown MoSe 2 , 32,33 and molecular beam grown MoSe 2 , [35][36][37] or in grain boundary of 2H phase, 21 or boundary of 2H and 1T phase, 28 in MoS 2 . In contrast, the second grain boundaries (denoted as green lines) comprise of chains of 8-fold rings.…”
Section: Atomic Structure Of Inversion Domains Grain Boundarysupporting
confidence: 74%
See 1 more Smart Citation
“…The rst grain boundaries (denoted as yellow lines) are composed of the chains of 4-fold rings (4|4) with point-sharing at a common Se site. This type of phase boundary has been previously observed in grain boundary of CVD-grown MoSe 2 , 32,33 and molecular beam grown MoSe 2 , [35][36][37] or in grain boundary of 2H phase, 21 or boundary of 2H and 1T phase, 28 in MoS 2 . In contrast, the second grain boundaries (denoted as green lines) comprise of chains of 8-fold rings.…”
Section: Atomic Structure Of Inversion Domains Grain Boundarysupporting
confidence: 74%
“…This result is consistent with the fact that 4|4 IDBs is oen observed in previous reports. 37,38,45 Recently, Zande et al showed that the measured in-plane electrical conductivity of the monolayer MoS 2 is slightly increased by the mid-gap states of Mo atoms at grain boundaries. 20 Therefore, it is important to understand how the 4|4and 8|8-fold rings contribute to electrical transport in the present IDBs model.…”
Section: Atomic Structure Of Inversion Domains Grain Boundarymentioning
confidence: 99%
“…In bilayer MoSe 2 and other group VIB TMDC films, the most thermodynamically stable stacking order is 2H which takes the AA' interlayer stacking sequence. Other stacking registries, such as 3R (AB), 2Ha (AB'), and fractional translated states, can be regarded as stacking faults in 2H‐based MoSe 2 crystals . Density functional theory (DFT) calculations suggest that the formation energy of bilayer 2H‐stacked MoSe 2 is 33 and 216 meV nm −2 lower than those of the 3R‐stacked and N‐stacked crystals (Figure S1, Supporting Information), respectively .…”
Section: Methodsmentioning
confidence: 99%
“…Other stacking registries, such as 3R (AB), 2Ha (AB'), and fractional translated states, can be regarded as stacking faults in 2H‐based MoSe 2 crystals . Density functional theory (DFT) calculations suggest that the formation energy of bilayer 2H‐stacked MoSe 2 is 33 and 216 meV nm −2 lower than those of the 3R‐stacked and N‐stacked crystals (Figure S1, Supporting Information), respectively . The N stacking order can be obtained from the 3R phase by gliding the top layer relative to the bottom layer for 95 pm along the armchair direction .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation